2019
DOI: 10.2118/199356-pa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geochemical Properties on Wettability of Kerogen and Organic-Rich Mudrocks

Abstract: Summary The wettability of organic-rich mudrocks has a significant effect on multiphase-fluid flow and hydrocarbon recovery. This important rock property has still not been well-quantified in organic-rich mudrocks. Kerogen constitutes a significant fraction of mudrocks and can considerably affect their wettability. Recent publications suggested that kerogen wettability is affected by the thermal maturity of rocks and can influence the wettability of mudrocks. In this paper, we experimentally qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This indicates that the Type II-C kerogen is generally nC 8 -wet, which is in line with the experimental finding for kerogen with high maturity. 68 In Fig. 6(c), we present the H 2 O density profile along the z -direction at X = 0.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the Type II-C kerogen is generally nC 8 -wet, which is in line with the experimental finding for kerogen with high maturity. 68 In Fig. 6(c), we present the H 2 O density profile along the z -direction at X = 0.…”
Section: Resultsmentioning
confidence: 99%
“…They expressed that the lack of OM pores in oil-mature samples is due to the bitumen infilling of pores. Even a low concentration of kerogen (e.g., 4 wt %) can significantly impact the water adsorption capacity and wettability of the organic-rich mudrocks . Therefore, the maturity (on the basis of the vitrinite reflectance) of OM affects the wetting affinity, as discussed in the following section.…”
Section: Effect Of the Organic Matter Content On Shale Wettabilitymentioning
confidence: 99%
“…Many researchers observed substantial contact angle variation within a small shale sample only a few millimeters apart. ,− Whereas the pores at the surface of the rock are artificially accessible and can drastically influence the observed contact angle, this method is not sufficient for characterizing the wettability of tight/shale rocks . Furthermore, the contact angle measurement may not realistically represent the actual reservoir ( in situ ) wettability in heterogeneous organic-rich rocks. , …”
Section: Reliability Of Conventional Approaches To Measure Wettabilit...mentioning
confidence: 99%
See 1 more Smart Citation
“…In some recent studies, Jagadisan and Heidari observed that thermal maturation induces variations in the kerogen’s chemical structure and modifies its oxygen and hydrogen content, which affects its wettability. Although the maturities of outcrop and subsurface shales are different, the variations in the measured wettabilities of outcrop and equivalent subsurface samples might be unexpected.…”
Section: Comparison Based On Geochemical Characteristicsmentioning
confidence: 99%